Mapping the Customer Experience Management Strategies for Customer Loyalty in Retail Hypermarket Jabodetabek - Logahan, Jerry Marcellinus; Meliala, Janita Sembiring; Putong, Iskandar (Journal The Winners, 2015)
Today, competition in the global market has become increasingly difficult and and at the same timeÂ products and services provided by retail companies tend to be similar. So in such circumstances, customersÂ expect not only satisfied with the products and services, but also the pursuit of the perfect shopping experienceÂ during the shopping process. The purpose of this study was to devise a customer experience managementÂ strategy at a hypermarket retailer Carrefour, Hypermart, Giant, and Lotte Mart. Both overall and per hypermarket retail chains that have the same character. The method used is Factor Analysis, Multi DimensionÂ Scaling (MDS). The object of research is the hypermarket retail customers in Jakarta, Bogor, Depok, TangerangÂ and Bekasi to sample 360 people. The results of MDS mapping CEM variable per retail hypermarket retailÂ hypermarket seen no one who is in the first quadrant in which the dimensions 1 and 2 positive namely Giant hypermarket retail. Tthere are three retail hypermarket located in quadrant 2 wherein the dimensions of 1Â positive and 2 negative dimension namely retail Carrefour, Hypermart and Lotte Mart. In MDS can be classifiedÂ Group 1 are the outlets; Group 1 are GPS (Giant Plaza Semanggi), CLB (Carrefour Lebak Bulus), CPHÂ (Carrefour Permata Hijau) and HPV (Hypermart Pejaten Village) which leads to a positive value. While otherÂ outlets in group 2 are CCB (Carrefour Cibinong Bogor), GBT (Giant BSD Tangerang), GMD (Giant Margo cityÂ Depok), HPB (Hypermart Pondok Gede Bekasi), HJT (Hypermart JACC Thamrin), LRP (Lotte Mart RatuÂ Plaza), LKG (Lotte Mart Kelapa Gading), LF (Lotte Mart Fatmawati) have in common in the lower quadrantÂ (negative).